PENERAPAN PIJAT OKSITOSIN UNTUK MENGATASI MASALAH KEPERAWATAN MENYUSUI TIDAK EFEKTIF PADA PASIEN POST SECTIO CAESAR DI RUANG OBSETRI RSUP DR.KARIADI SEMARANG - Setyorini, Novi; Hastuti, Witri (NHM PRESS, 2024)
Background: Caesarean Section (CS) is an action carried out to give birth to a baby through surgery on the abdomen and uterine wall. The obstacles to breastfeeding that occur in postpartum caesarean section mothers are caused by postoperative pain that disturbs the mother's comfort and can inhibit the work of the posterior putative gland nerves that produce the hormone oxytocin which plays a role in the lactation process. Oxytocin massage is one of the solutions applied to overcome the lack of smooth breast milk. In addition, it is interpreted as a massage on the spine to the fifth-sixth costae bone to stimulate the oxytocin and prolific hormones after giving birth, the function of this massage is to increase the oxytocin hormone which can make the mother calm, so that breast milk will automatically come out Objective: to provide nursing care to post-Cesarean section clients with ineffective breastfeeding nursing problems by administering oxytocin massage.Method : using descriptive methods, namely case studies used on a group of objects Results: he problem of ineffective breastfeeding nursing experienced by Mrs. M and Mrs. C After oxytocin massage was performed, there was a change or increase in breast milk production in Mrs. M and Mrs. C. Suggestion: It is expected to be able to develop capabilities in the field of maternity health with non-pharmacological therapy, namely oxytoin massage in providing nursing care to postpartum mothers with ineffective breastfeeding problems.